2003
DOI: 10.2135/cropsci2003.8070
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Inbred and Hybrid Grain Yield under Stress and Nonstress Environments in Tropical Maize

Abstract: Drought and low soil N cause significant yield reductions in maize (Zea mays L.) grown in the tropics. Understanding the genetic basis of hybrid performance under these stresses is crucial to designing appropriate breeding strategies. This study evaluates under optimal, drought and low N stress conditions (i) the performance, combining abilities and stability of a group of tropical white inbred lines; (ii) the genetic control and modes of gene action for grain yield; and (iii) the relationship between line per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
129
4
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(185 citation statements)
references
References 38 publications
34
129
4
5
Order By: Relevance
“…Furthermore, non-additive gene effect was predominant in the control of grain yield, anthesis-silking interval, leaf chlorophyll content and ear aspect while days to silking, leaf senescence and plant height were influenced mainly by additive gene effects. Similar results on grain yield were earlier reported by Betràn et al (2003), Gama et al (2002), Mosisa et al (2008), Makumbi et al (2011), Meseka et al (2006, 2013, and Ndhlela (2012). However, these results are contradictory to those of Below et al (1997), Kling et al (1997), Badu-Apraku et al (2011, 2013, Ifie et al (2014) and Tamilarasi et al (2010) who reported predominance of additive gene effects compared to non-additive gene effects for grain yield under low N. The contradictory results might be due to the difference in environments (N stress level) under which the genotypes were tested or genotypic differences among sets of genotypes included in the studies as suggested by Mosisa et al (2008).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, non-additive gene effect was predominant in the control of grain yield, anthesis-silking interval, leaf chlorophyll content and ear aspect while days to silking, leaf senescence and plant height were influenced mainly by additive gene effects. Similar results on grain yield were earlier reported by Betràn et al (2003), Gama et al (2002), Mosisa et al (2008), Makumbi et al (2011), Meseka et al (2006, 2013, and Ndhlela (2012). However, these results are contradictory to those of Below et al (1997), Kling et al (1997), Badu-Apraku et al (2011, 2013, Ifie et al (2014) and Tamilarasi et al (2010) who reported predominance of additive gene effects compared to non-additive gene effects for grain yield under low N. The contradictory results might be due to the difference in environments (N stress level) under which the genotypes were tested or genotypic differences among sets of genotypes included in the studies as suggested by Mosisa et al (2008).…”
Section: Discussionsupporting
confidence: 90%
“…The development of inbreds having high combining abilities has a fundamental role in the efficient use of heterosis (Vasal et al, 1992). Crossing between inbred lines with high specific combining ability can improve tolerance to different stresses and superior hybrids with high yield production under stress condition (Betràn et al, 2003;Vasal et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mid-altitude zone falls within the altitudinal range of between 1000 and 1800 masl and it is characterized by rainfall of more than 500mm and mean temperature of 21.5 o C. The social-economic constraints, such as high inorganic fertilizer costs and lack of credit for small scale farmers ) are further worsening the bio-physical constraints that are hampering maize production. Hence development of maize hybrids that can adapt to these stresses is important (Hoisington, 2001;Betrán et al, 2003;Bӓnziger et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The study identified eight drought and low-N tolerant three-way hybrids which yielded 24, 15 and 64% more than the best hybrid checks under optimum, low-N and drought stress conditions, respectively. Betrán et al (2003) also did a study to evaluate a group of tropical white inbred lines for grain yield performance, combining abilities and stability under optimal, drought and low-N stress conditions. They found heterosis to increase with the intensity of drought stress.…”
Section: Introductionmentioning
confidence: 99%